IODP Expedition 361 Spectrophotometry - Hall, I.R.; Hemming, S.R.; LeVay, L.J.; Barker, S.; Berke, M.A.; Brentegani, L.; Caley, T.; Cartagena-Sierra, A.; Charles, C.D.; Coenen, J.J.; Crespin, J.G.; Franzese, A.M.; et al. (Zenodo, 2020)
Interstitial water constitutents were measured by UV-VIS spectrometry using colorimetric methods (e.g., ammonium, nitrate, nitrite, phosphate, silica, and sulfide) by an Agilent CARY 100 UV-VIS spectrophotometer.